COST Action C26 : urban habitat constructions under catastrophic events : proceedings of the Final Conference (Naples, 16, 17, 18 September 2010) : proceedings of the Final COST Action C26 Conference, Naples, Italy, 16-18 September 2010 /: urban habitat constructions under catastrophic events : proceedings of the Final Conference (Naples, 16, 17, 18 September 2010) : proceedings of the Final COST Action C26 Conference, Naples, Italy, 16-18 September 2010. (©2010) - Unknown
No abstract available